2005
DOI: 10.5432/ijshs.3.143
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Elastic Properties of Human Tendon Structures in Lower Limb

Abstract: The present study was conducted to evaluate the elastic properties of human tendon structures and their influences on human movements, and to investigate the effects of resistance training on tendon properties. During isometric contraction, the elongations of tendon structures in knee extensors and plantar flexors were measured by means of real-time ultrasonography. The resulting tendon force and elongation relationship was non-linear in form, as previously reported on animal and human cadaver tendons in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…5). We also previously reported that tendon stiffness in knee extensors was inversely correlated with the relative difference in jump height between vertical jumps performed with and without countermovement (Kubo et al 1999;Kubo 2005). However, according to the correlation coefficient of r = -0.471 for CMJ and r = -0.502 for DJ between the two parameters, the tendon stiffness only accounted for 22-25% of the variance in the pre-stretch augmentation.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…5). We also previously reported that tendon stiffness in knee extensors was inversely correlated with the relative difference in jump height between vertical jumps performed with and without countermovement (Kubo et al 1999;Kubo 2005). However, according to the correlation coefficient of r = -0.471 for CMJ and r = -0.502 for DJ between the two parameters, the tendon stiffness only accounted for 22-25% of the variance in the pre-stretch augmentation.…”
Section: Discussionmentioning
confidence: 71%
“…However, the previous studies (Kubo et al 1999;Kubo 2005;Bojsen-Moller et al 2005) included some flaws. First, jump tests taken in the previous studies consisted of multi-joint movements, and so it was difficult to specify the muscles mainly acting to perform the task.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A previous investigation [34] has shown that the association of resistance and flexibility training decreases MTU hysteresis more than resistance training alone. Hysteresis is defined as the energy lost as heat during stretching of viscoelastic materials [47]. A decrease in hysteresis following chronic stretching provides an indication that adequate flexibility may improve performance in dynamic activities.…”
Section: The Influence Of Chronic Stretching On Muscle Flexibility Anmentioning
confidence: 99%